A pre-service teacher’s view on emergency remote education in rural Nova Scotia: A scoping review of literature on digital equity as illuminated by COVID-19 - Kettley, Meagan; Mitton, Jennifer (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2025)
This article presents a scoping review of literature on the impact of emergency remote education in low-income rural settings to contextualize the experiences in rural Nova Scotia during the COVID-19 pandemic. The initial literature reviewed included 37 articles across Western nations, the majority subscribing to an investigative methodology with participant interviewing, field observations, and in-depth reviews of literature as the most common sources of data collection. Due to the unprecedented nature of COVID-19, little is known about this topic. This review provides insights into the experiences of emergency remote education in low-income rural communities from the perspective of students, pre- and in-service teachers, and rural education stakeholders, and suggests a need for integrating pandemic-informed rural pedagogy into teacher education programs.